Biochemical changes throughout grape berry development and fruit and wine quality - Conde, C. (2007)
Wine is made up of more than one thousand compounds, the majority of which, such as vitamins and minerals, come from the grapes, while others, like ethanol and glycerol, are products of the winemaking process. Although sugars are either partially or completely transformed, sugar import and accumulation into the ripening berry is a major parameter of wine quality. Sugar status is directly related to the final alcoholic content of wine, and regulates several genes responsible for the development of its aromatic and organoleptic properties. Physiological ripeness is reached when the grapes achieve sufficiently high sugar levels without loosing too much acidity; however, aromatic and phenolic compound content must also be taken into account. Softening and water content are other essential characteristics of a ripe berry. From a winemaker point of view, optimal grape maturity is essential for wine quality, but is difficult to assess because it is under multifactorial control, involving grapevine cultivar variety and environmental parameters such as soil, temperature, exposure to sun, and hormonal regulation. Continued study of the key control points in grape ripening is crucial if we ultimately hope to improve grape and wine quality.